Prolonged Anaphylaxis to Pfizer Coronavirus Disease 2019 Vaccine: A Case Report and Mechanism of Action. (2nd April 2021) - Frank, Ashleigh; Radparvar, Sara; Manasia, Anthony; Bassily-Marcus, Adel; Kohli-Seth, Roopa
Abstract : Background: In response to the devastating effects of the coronavirus disease 2019 pandemic, several vaccine prototypes have been developed, with the Pfizer/BioNTech (BNT162b2) platform being the first to receive emergency use authorization. Although taken to market on an unprecedented timeline, the safety profile of the drug during clinical trials was shown to be favorable. Shortly after release, reports from the Centers for Disease Control and Prevention demonstrated a higher-than-average rate of anaphylaxis to the vaccine that has been the cause for concern for safety officials and the general public alike. Here, we present a unique case of protracted anaphylaxis in a recipient of the BNT162b2. Case Summary: The patient is a 55-year-old female with a history of multiple allergic reactions who presented with respiratory distress and hives after receiving the first dose of the BNT162b2, despite premedication with IV steroids and diphenhydramine. The refractory nature of her reaction was demonstrated by edema of her tongue (visualized on nasolaryngoscopy), requiring an epinephrine infusion for nearly 3 days. She was discharged from the hospital with instructions not to receive the second dose of the vaccine. Conclusion: Although the exact etiology of anaphylaxis secondary to this messenger RNA-based vaccine is not completely clear, our literature search and review of the patient's course support either polyethylene glycol versus other excipient-related allergy as a possible cause. Based on the protracted nature to our patient's anaphylaxis, critical care management for patients with a true anaphylactic reaction to BNT162b2 may require monitoring for an extended period of time.